2007
DOI: 10.1371/journal.pbio.0050185
|View full text |Cite
|
Sign up to set email alerts
|

A Dendrite-Autonomous Mechanism for Direction Selectivity in Retinal Starburst Amacrine Cells

Abstract: Detection of image motion direction begins in the retina, with starburst amacrine cells (SACs) playing a major role. SACs generate larger dendritic Ca2+ signals when motion is from their somata towards their dendritic tips than for motion in the opposite direction. To study the mechanisms underlying the computation of direction selectivity (DS) in SAC dendrites, electrical responses to expanding and contracting circular wave visual stimuli were measured via somatic whole-cell recordings and quantified using Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
189
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(216 citation statements)
references
References 82 publications
17
189
3
Order By: Relevance
“…Data were analyzed using Fourier analysis (cf. Hausselt et al, 2007). We took the voltage trace during the sinusoidal light stimulation, discarded the first second (to avoid initial transients) (see Fig.…”
Section: ϫ2mentioning
confidence: 99%
“…Data were analyzed using Fourier analysis (cf. Hausselt et al, 2007). We took the voltage trace during the sinusoidal light stimulation, discarded the first second (to avoid initial transients) (see Fig.…”
Section: ϫ2mentioning
confidence: 99%
“…There is ample evidence that neurons are highly sensitive coincidence detectors and can distinguish between precisely coinciding and temporally dispersed inputs (Bi and Poo, 1998;Usrey et al, 2000;Ahissar and Arieli, 2001;Azouz and Gray, 2003;London and Häusser, 2005;VanRullen et al, 2005;Meliza and Dan, 2006;Fries et al, 2007;Hausselt et al, 2007;Tsubo et al, 2007;Cardin et al, 2009;Branco et al, 2010). By switching positions in the firing sequence, the inputs to target cells can either coincide or disperse in time, and in the case of dispersion, the sequence can change.…”
Section: Potential Readout Mechanismsmentioning
confidence: 99%
“…By switching positions in the firing sequence, the inputs to target cells can either coincide or disperse in time, and in the case of dispersion, the sequence can change. This, too, is a relevant variable for postsynaptic activity, because it matters whether EPSPs at distal dendritic compartments are generated before or after those at proximal sites (London and Häusser, 2005;Hausselt et al, 2007;Branco et al, 2010) (supplemental Fig. S11 F, G, and supplemental Discussion 2, available at www.jneurosci.org as supplemental material).…”
Section: Potential Readout Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it has demonstrated that direction selectivity originates in complex subcellular interactions between the dendrites of starburst amacrine cells (SACs) arrayed in a laminar fashion around the directionally selective ganglion cells (DSGCs). The design of the underlying retinal circuitry is understood in broad terms [124,125], but it is still not clearly understood how the directionally selective signal is actually computed [33,48].…”
Section: Introductionmentioning
confidence: 99%